Analisis Sebaran Total Suspended Solid dengan Tingkat Keasaman Laut di Wilayah Pesisir Pulau Lusi Sidoarjo Menggunakan Citra Satelit Landsat-8 - I Dewa Made Satria Darma Guna; Siti Zainab (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
Indonesia has an area of ​​around 1,904,569km² with the largest archipelago in the world, namely 17,508 islands. One of the islands formed from sediment is in Sidoarjo Regency, East Java Province due to the Lapindo mud phenomenon from 2006 until now. Over the years, the overflowing mud was directed into the Porong River, resulting in Lusi Island. Lusi Island and its surroundings, including the coast of the island, is maximized through science and technology such as remote sensing from Landsat-8 The aim of this research is to analyze the distribution of Total Suspended Solid (TSS) and sea water acidity (PH) in the coastal area of ​​Lusi Island. The analysis results show that the field data values ​​taken in May 2024 for total suspended solids were 100 mg/L – 80 mg/L and for sea water acidity levels were 8.2 – 8.1. Meanwhile, the total suspended solid image data is 51.79 mg/L – 107.76 mg/L and the acidity level of sea water is 8.05 – 8.53.